Financing constraints and R&D investments of large corporations in Europe and the USA - Michele Cincera; Julien Ravet (European Commission, Joint Research Centre (JRC), 2010)
This paper explores the existence and importance of financing constraints for R&D investments in large EU and US manufacturing companies over the 2000 – 2007 period. The main results obtained by estimating error-correction equations suggest that the sensitivity of R&D investments to cash flow variations are important for European firms while US ones do not appear to be financially constrained. In terms of policy implications, these results suggest improving the conditions for access to external capital to finance R&D activities in the EU.
Keywords: C23; E22; O31; 330; Financial constraints; R&D investments; error-correction investment equations; system GMM panel data econometric models